Upwelling phenomena: the main driver of the latitudinal diversity pattern in Northwest Africa? - Ramos, Ana; Ramil, Francisco; García-Isarch, Eva; Matos-Pita, Susana Soto de; Castillo, Sara; Gil, Marta; Calero, Belén; Muñoz, Isabel; Rocha, Francisco; Fernández-Gago, R. (2015)
Although some depth-related patterns of the continental margin biodiversity are currently understood, the hypothesis that support the latitudinal gradient of species richness increasing from poles to tropics, has only been tested for particular North Atlantic taxa. To date, no systematic and comparative research considering the global zoobenthos at a large regional scale has been undertaken and therefore, the existence of a latitudinal large scale pattern remains uncertain worldwide. Despite the knowledge on benthic biodiversity of Northwest African slope is currently very scarce, some authors pointed out that faunal richness is higher in the upwelling areas than in the tropical regions, being probably less influenced by latitude than by upwelling phenomena and seasonal displacements of thermal fronts occurring in the so-called ‘alternance’ regions. The intensive sampling program following identical methodology in the Canary Current Large Marine Ecosystem region between 2002 and 2012 within the framework of the EcoAfrik and FAO EAF-Nansen projects, offered a unique overview of the biodiversity patterns along the Northwestern African deep-shelf and slope. This approach is based on the taxonomic identification of large collections and the analysis of quantitative data from the benthic invertebrates taken in 1350 trawl stations carried out throughout the 11 research surveys onboard R/V Dr. Fridtjof Nansen and R/V Vizconde de Eza. Preliminary results of these surveys did not show a diversity pattern directly related to latitude along the Northwestern African slope. Specific richness increases significantly along the Moroccan and Saharan coasts, from Cape Spartel (Gibraltar Strait) to Cape Blanc, but decreasing southwards along the Mauritanian continental margin. The highest specific richness values are recorded along the Saharan slope (mean = 36 species by station versus mean = 22–23 species per station in the southern region). The global megabenthic richness and the proportion of suspension-feeders are both higher ...